Animal models and high field imaging and spectroscopy - Öz, Gülin (Les Laboratoires Servier, 2013)
A plethora of magnetic resonance (MR) techniques developed in the last two decades provide unique and noninvasive measurement capabilities for studies of basic brain function and brain diseases in humans. Animal model experiments have been an indispensible part of this development. MR imaging and spectroscopy measurements have been employed in animal models, either by themselves or in combination with complementary and often invasive techniques, to enlighten us about the information content of such MR methods and/or verify observations made in the human brain. They have also been employed, with or independently of human efforts, to examine mechanisms underlying pathological developments in the brain, exploiting the wealth of animal models available for such studies. In this endeavor, the desire to push for ever-higher spatial and/or spectral resolution, better signal-to-noise ratio, and unique image contrast has inevitably led to the introduction of increasingly higher magnetic fields. As a result, today, animal model studies are starting to be conducted at magnetic fields ranging from ~ 11 to 17 Tesla, significantly enhancing the armamentarium of tools available for the probing brain function and brain pathologies.